Biometria de frutos e sementes, germinação e ecologia populacional de Dalbergia nigra (vell.) allemão ex benth. (Fabaceae) em um fragmento urbano de floresta estacional semidecidual em Uberlândia, MG - Costa, Rosane Oliveira (2011)
The invasion of natural ecosystems by exotic species is considered the second bigger worldwide threat to biodiversity. The bigger the degree of disturbance of a natural ecosystem, the bigger the potential of dispersion and establishment of these species, mainly after the strong effect caused by the fragmentation process. The research was carried in a fragment of seasonal semideciduous forest in Uberlândia, Minas Gerais located in Parque Municipal do Sabiá . The aim of this study was to evaluate the invasion potential of Dalbergia nigra (Vell.) Allemão Benth. (FABACEAE), an introduced non-native species used for arborization around the forest fragment. We made biometrics measures of fruits and seeds from five different individuals, evaluated the quality of the seeds and we still tested the germination power of naked seeds and fruits just collected and stored for approximately one year. The dispersion reach and establishment of the individuals inside of fragment was verified through the counting of individuals throughout six transects, being three of them located next the sources of dispersion and others three distant ones to the sources. Moreover, we made a study of structure and dynamics of the population throughout four years (From 2008 to 2011), with annual measures of diameter and height and calculation of the conscription taxes, mortality and growth in forty parcels of 10x10m. Seeds were found intact, damaged and deformed. The biometrics measures of fruits and seeds pointed indications of genetic variation between the individuals. It was observed high taxes of germination, even for stored seeds, with reduction of about 50% of the initial taxes. The dispersion reach and establishment whe strong related to the sources of dispersion in the transects located next to them, while in the other transects the number of individuals was significantly lower and the distribution is more random, probably being related to a bigger investment in dispersion and still to the action of ants while secondary dispersers. The structure of the population in 2008 presented a total of 67 individuals. Throughout the period of accompaniment it had fluctuations in the conscription and mortality taxes, with continuous growth taxes and positive annual conscription. All the results showed indications of invasive potential of the species in the study area, although D. nigra is an endangered species in its area of natural occurrence. The presence of non-native species in the region shows the vulnerability of the studied forest community in the current period of natural recovery, after historical actions of inadequate management.